"Word and World: Luther Across Borders" The 14th International Congress for Luther Research, Thousand Oaks, California, 2022. Issue 3 (13th October 2022) - Leppin, Volker; Stjerna, Kirsi
Abstract: Reporting on the 14th International Congress for Luther Research, "Word and World: Luther across Borders, " held in Thousand Oaks, California, on August 14–19, 2022, with brief reflections on the history, rationale, and organization of the Congress, as well as on future opportunities for Luther scholarship to engage.